Factors Affecting Consumer Buying Behavior towards Local Brands in Zambia: A Consideration of the Product Preference - Mweemba, Burton; Mweshi, Dr. Geoffrey; Bbenkele, Professor Edwin (RA Journal of Applied Research, 2022)
Recent economic growth trends in Africa have heightened industry awareness of the market potential of many African countries including Zambia. As a result, academics are becoming increasingly interested in learning about African customers' attitudes, tastes, and behavior. The majority of the investigations on the factors affecting consumer behavior have been done predominantly from the Western marketing viewpoints, and the results have been informative in the sense that they confirmed and extended existing marketing models. In view of this, this paper brings out the Zambian perspective of consumer buying behavior. There has been an increase in the sale of imported FMCGs in Zambia, hence this motivated the investigation on the factors that motivate consumers when buying the products. The results indicate that quality, price, and availability influence consumer buying behavior in Zambia. The results further suggest that consumers in Zambia prefer imported FMCGs. The recommendation, therefore, is that manufacturers should take into consideration the factors affecting consumer behavior when producing FMCGs. The gap in understanding consumer buying behavior in less developed countries like Zambia has existed since 1986 when Bbenkele (1986) found that product shortages had an impact on brand loyalty in Zambia.